AGRESIVITAS TOKOH DALAM CERPEN QALBU IMRA’ATIN KARYA NAJIB KAILANI - Zuriyati Zuriyati (Adabiyyāt: Jurnal Bahasa dan Sastra, 2012)
Short story as literary creation is an expression of the author’s response toward the external realities and conflicts. Those conflicts extend from social to domestic conflicts. Qalbu Imra’atin (Woman’s Heart) captures the domestic conclict of a wife and her aggressive husband. Agression is is reactionary and impulsive behavior that often results in breaking household rules or the law; aggressive behavior is violent and unpredictable. To approach this kind of behaviour in literary work literary psychology is needed. Therefore this resarch aims to know more about what, how, effect, as well as the solution of aggression experienced by the characters in Qalbu Imra’atin (Woman’s Heart).